A Trial of Treatment for Acute Otorrhea in Children with Tympanostomy Tubes - van Dongen, Thijs M.A; van der Heijden, Geert J.M.G; Venekamp, Roderick P; Rovers, Maroeska M; Schilder, Anne G.M (The New England journal of medicine, 2014)
Appropriate treatment of acute uncomplicated otorrhea in children with tympanostomy tubes is unclear. In this trial involving 230 children in the Netherlands, antibiotic–glucocorticoid eardrops were superior to oral amoxicillin–clavulanate or initial observation. The insertion of tympanostomy tubes is one of the most frequently performed surgical procedures in children. 1 The main indications for this procedure are the restoration of hearing in children with persistent otitis media with effusion and the prevention of recurrences in children who have recurrent acute otitis media. 2 Acute otorrhea is a common sequela in children with tympanostomy tubes, with reported incidence rates ranging from 26% in a meta-analysis of mainly observational studies (involving cases of clinically manifested otorrhea) to 75% in a randomized trial (which included asymptomatic and subclinical cases). 3 – 5 Acute tympanostomy-tube otorrhea may be accompanied by foul . . .